The correlation between fruit intake and all-cause mortality in hypertensive patients: a 10-year follow-up study - Sun, Chuang; Li, Jie; Zhao, Zeyuan; Ren, Shupeng; Guan, Yue; Zhang, Miaoan; Li, Tianfeng; Tan, Linglin; Yao, Qiying; Chen, Liang (Frontiers in Nutrition, 2024)
Objective: Extensive research has consistently shown the beneficial impact of fruit consumption on overall health. While some studies have proposed a potential association between fruit consumption and hypertension management, the influence of fruit consumption on mortality rates among hypertensive individuals remains uncertain. Consequently, aim of this study is to evaluate whether fruit consumption is associated with all-cause mortality among hypertensive patients. Methods: Data were obtained from the National Health and Nutrition Examination Survey (NHANES), conducted between 2003 and 2006. Ten-year follow-up data from the National Death Index (NDI) were used to assess all-cause mortality. Cox proportional hazard model was utilized to explore the impact of fruit intake on all-cause mortality among hypertensive individuals. Results: The study included a cohort of 2480 patients diagnosed with hypertension, and during the follow-up period, a total of 658 deaths from various causes were recorded. The COX regression analysis demonstrated that hypertensive patients who consumed apples three to six times per week exhibited a significantly reduced risk of all-cause mortality (HR=0.60, 95%CI: 0.45-0.78, P<0.001) in comparison to those who consumed apples less than once per month. Likewise, consuming bananas three to six times per week also led to a comparable outcome (HR=0.76, 95%CI: 0.59-0.97, P=0.027). Moreover, Combined consumption of bananas and apples three to six times per week exhibited a noteworthy decrease in all-cause mortality (HR=0.57, 95%CI: 0.39-0.84, P=0.004) when compared to individuals who consumed these fruits less frequently. Conversely, no significant association was found between the consumption of other fruits, including pears, pineapples, and grapes, and all-cause mortality. Conclusion: The study discovered that moderate consumption of apples and bananas was associated with a reduced risk of all-cause mortality in patients with hypertension. Keywords: Fruit consumption, Apple consumption, Banana consumption, Hypertension，All-cause mortality